Place-making in higher education: co-creating engagement and knowledge practices in the networked age. Issue 1 (2nd January 2016) - Swist, Teresa; Kuswara, Andreas
ABSTRACT: The pedagogical locations, functions and possibilities of higher education continuously unfold as mobile technologies, digital content and social practices intersect at a rapid pace. There is an urgent need to understand better how student learning is situated within this complex system and interrelates with broader sociotechnical knowledge practices. A geo-phenomenology optic frames this paper, exploring how activity system and affordance theories assist in highlighting the interconnections between online, offline and blended learning environments. Introduced is a theoretical notion of 'place-making' which frames how different depths, patterns and modes of learning engagement emerge from the activity system of personal, material and social affordances. It is argued that fostering engagement and co-creating knowledge practices hinge upon increasing awareness of how these nested affordances interrelate with one another. The proposed 'place-making framework' has implications for how activity systems of learning, teaching, assessment and research can be integrated meaningfully within pedagogy for the networked age.